Online Food Frequency Questionnaire From the Cohort of Universities of Minas Gerais (CUME Project, Brazil): Construction, Validity, and Reproducibility - Azarias, Heloísa Gambarelli de Araújo; Marques-Rocha, José Luiz; Miranda, Aline Elizabeth da Silva; dos Santos, Luana Caroline; Gomes Domingos, Ana Luíza; Hermsdorff, Helen Hermana Miranda; Bressan, Josefina; Oliveira, Fernando Luiz Pereira de; Leal, Arieta Carla Gualandi; Pimenta, Adriano Marçal (Frontiers in Nutrition, 2021)
Background: The Food Frequency Questionnaire (FFQ) is usually used in epidemiological studies to assess the food consumption. However, FFQ must have good accuracy, requiring its validation and reproducibility for the target population. Thus, the aim of this study was to describe the construction of the online Food Frequency Questionnaire (oFFQ) used at the Cohort of Universities of Minas Gerais (CUME project, Brazil) and evaluate its validity and reproducibility. Methods: The oFFQ was answered twice in one year (March/August 2018 – March/April 2019; n = 108 participants – reproducibility) and four 24-hour dietary recalls (24hRs) were applied in two seasons of the southern hemisphere [two 24hRs in autumn (March/June 2018) and two 24hRs in winter (August/September 2018); n = 150 participants – validity]. To assess the validity and reproducibility, the intraclass correlation coefficients (ICCs) were estimated. Results: The oFFQ had 144 food items separated into eight groups (dairy products; meat and fish; cereals and legumes; fruits; vegetables; fats and oils; drinks; other foods). In assessing validity, intraclass correlation coefficients (ICCs) for energy and macronutrients were considered moderate, ranging from 0.41 (energy) to 0.59 (protein); while micronutrients’ ICCs were considered low to moderate, ranging from 0.25 (fibres) to 0.65 (vitamin B6). Regarding reproducibility assessment, ICCs for energy and all assessed items were considered moderate to excellent, ranging from 0.60 (vegetables) to 0.91 (vitamin E and retinol). Conclusions: The self-reported oFFQ had satisfactory validity and reproducibility. So, it can be used to analyse the association between food consumption and chronic diseases in participants of CUME project.